Implementation of Problem Based Learning Methods in Student Spelling Learning - Fransisca Dwi Harjanti; Ni Luh Ramayani (Universitas Muhammadiyah Gresik, 2020)
In the Indonesian Language curriculum, especially those in the Indonesian Language curriculum usedat the High School level of Class X Science, one of the basic competencies discussed is writing theobservation report text. In writing a text report the results of observation require the ability of thelanguage field, specifically the ability to use spelling. To give students a good understanding ofspelling, special strategies are needed. Strategies that can be used to explore students' competenciesin the spelling field are problem based learning. In this strategy students are required to be moreactive and creative in solving problems given by the teacher. This strategy is applied to students ofClass X Science 2 at Hang Tuah 4 Surabaya High School. After applying problem-based learningbased on the results obtained that the average ability of students in understanding spelling is above75%. Only a small proportion of groups whose ability is under 75%. The most mistake students makeis in using comma (,) punctuation. The least mistake made is the use of period punctuation